2018
DOI: 10.1093/bioinformatics/bty235
|View full text |Cite
|
Sign up to set email alerts
|

A spectral clustering-based method for identifying clones from high-throughput B cell repertoire sequencing data

Abstract: MotivationB cells derive their antigen-specificity through the expression of Immunoglobulin (Ig) receptors on their surface. These receptors are initially generated stochastically by somatic re-arrangement of the DNA and further diversified following antigen-activation by a process of somatic hypermutation, which introduces mainly point substitutions into the receptor DNA at a high rate. Recent advances in next-generation sequencing have enabled large-scale profiling of the B cell Ig repertoire from blood and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(103 citation statements)
references
References 30 publications
1
100
2
Order By: Relevance
“…Caveats should be noted given that our results rely on tracing B cell clones by analysis of their IGH V(D)J sequences alone. While we (and others) have demonstrated that clonal relationships can be reliably inferred given the diversity of IGH V(D)J sequences, false positives may occur (43,67,68). Additionally, owing to the abundance of transitional B cells that re-populate the repertoire during RTX relapse and our interest in studying antigen-experienced B cell subsets, we specifically excluded IgD+ expressing B cell subsets from our single-cell analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Caveats should be noted given that our results rely on tracing B cell clones by analysis of their IGH V(D)J sequences alone. While we (and others) have demonstrated that clonal relationships can be reliably inferred given the diversity of IGH V(D)J sequences, false positives may occur (43,67,68). Additionally, owing to the abundance of transitional B cells that re-populate the repertoire during RTX relapse and our interest in studying antigen-experienced B cell subsets, we specifically excluded IgD+ expressing B cell subsets from our single-cell analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The original distance-based model for identification of B cell clones used by SCOPer measures distance using the junction region of the BCR (Nouri and Kleinstein, 2018b). The junction includes the CDR3 along with the two flanking amino acids (one 5 that is encoded by IGHV, and one 3 that is encoded by IGHJ) (Lefranc, 2014).…”
Section: The Stress-based Methods Improves the Sensitivity Specificitmentioning
confidence: 99%
“…This model is implemented in the new version of SCOPer. The first version of SCOPer, a spectral clustering-based method for identifying clones from high-throughput B cell repertoire sequencing data, was presented in Nouri and Kleinstein (2018b). In the following sections, we discuss the main steps of the methodology and explain our implementation of the recent improvements upon the original framework.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…A hamming distance is calculated on the junction regions of pairs of sequences in each of the groups separately. Finally, distances are fed into a clustering algorithm (Hierarchical [1] or Spectral [2]). Here, we propose to use a tf-idf based distance that bypasses the three steps prior to clustering, and is not restricted to sequences with the same V or J gene or junction length.…”
Section: Introductionmentioning
confidence: 99%